2021
DOI: 10.3390/children8100926
|View full text |Cite
|
Sign up to set email alerts
|

Complex Evaluation of Tissue Factors in Pediatric Cholesteatoma

Abstract: The aim of this study was to describe the appearance and distribution of tissue remodeling markers (MMP-2, MMP-9, TIMP-2, TIMP-4), Sonic hedgehog gene protein (Shh), pro- and anti-inflammatory cytokines (IL–1, IL–10), transcription factor (NF-κβ), proliferation marker (Ki–67), angiogenetic factor (VEGF), tissue defensins (HβD–2, HβD–4) of the pediatric cholesteatoma. Sixteen cholesteatoma samples were obtained from children, eleven skin controls from cadavers. Tissues were stained for MMP-2, MMP-9, TIMP-2, TIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Furthermore, a significant correlation was found between TLR4 and activated NF-κB [ 37 ] in MEC tissue, and we assume, that the same could be shown for RAGE as well. Further, another study demonstrated a correlation between NF-kB and biomarkers of angiogenesis and osteolysis in MEC tissue isolated from patients [ 84 ]. In addition to this, the DNA-binding protein inhibitor Id1, known to be induced by chronic TLR4 signalling [ 85 ], was proven to be abundantly expressed in MEC epithelium [ 86 ] where it accelerates proliferation and survival of keratinocytes in vitro via NF-κB signalling [ 87 ].…”
Section: Applicable Targets In Precision Medicine For Mec Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a significant correlation was found between TLR4 and activated NF-κB [ 37 ] in MEC tissue, and we assume, that the same could be shown for RAGE as well. Further, another study demonstrated a correlation between NF-kB and biomarkers of angiogenesis and osteolysis in MEC tissue isolated from patients [ 84 ]. In addition to this, the DNA-binding protein inhibitor Id1, known to be induced by chronic TLR4 signalling [ 85 ], was proven to be abundantly expressed in MEC epithelium [ 86 ] where it accelerates proliferation and survival of keratinocytes in vitro via NF-κB signalling [ 87 ].…”
Section: Applicable Targets In Precision Medicine For Mec Therapymentioning
confidence: 99%
“…The most prominent is the vascular endothelial growth factor (VEGF), for which expression is upregulated in compared to normal skin [ 241 , 282 ]. A correlation between NF-κB driven inflammation and VEGF was shown to promote the neovascularisation in MEC tissue [ 84 ]. VEGF signalling can be inhibited by approved drugs on the level of intracellular signalling by drugs like sunitinib [ 288 ] or axitinib [ 289 ], which are approved for treatment of renal cell carcinoma or nintedanib applied against pulmonary fibrosis [ 290 ] or lucitanib used in clinical trials against cancer [ 291 ].…”
Section: Applicable Targets In Precision Medicine For Mec Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…However, additional information on how HβD-2 acts in cholesteatoma tissue is needed. There are limited data about the importance of HβD-4 in cholesteatoma, but our previous study showed that HβD-2 is more heavily expressed in pediatric cholesteatoma tissue than HβD-4 [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chiang et al proved that the loss of Shh causes external- and middle -ear pathologies [ 28 ]. However, the exact role of Shh in cholesteatoma tissue is not yet clear, although our previous study showed the upregulation of Shh in cholesteatoma compared to skin tissue [ 26 ].…”
Section: Introductionmentioning
confidence: 99%